Public self-consciousness and group identification on buying preference. - Tan, Elsa Hin Hui. (2011)
The current literature has established that public self-consciousness, the disposition to think about how the self is perceived by others, is a predictor of buying reference. As compared to low public self-consciousness, high public self-consciousness has been reported to predict a greater preference for products that enhance the public images of the individual. The present study investigated this effect and did not find support for previous findings. The effect of public self-consciousness on buying preference was further examined with respect to group identification. A moderating effect of group identification was found in the study, suggesting possible avenues for future research.